Re-reading Vsevolod Ivanov’s Story “The Armored Train 14-69” Against Siberian Periodicals (1919): The historical comment of the Russian allies in the Civil War - Elena A. Papkova (Studia Litterarum)
The essay discusses the role that the allied powers — United States, France, Britain, and Japan — played in the development and in the collapse of the Admiral A.V. Kolchak’s anti-Bolshevik Russian government between 1918 and 1920. The discussion is based on the material of the hitherto unknown newspaper publications by Vsevolod Ivanov issued in 1919 by a military newspaper Vpered (Forward) and his literary works. The latter include his classic story about the Civil War entitled “The Armored Train 14-69” (1921), the homonymous plays (1927), and the screenplay (1963). For the first time, the article closely examines Ivanov’s cooperation with the newspaper Forward. The newspaper’s editor, Colonel V.G. Yanchevetsky, supported the government in major political questions. Ivanov’s articles “Bonds of friendship” (1919. September 26) and “‘Go’ and ‘Captain’” (1919. October 16) represent polar views on the role that the allies of the Russian government played in the Civil War. The first article underlines the importance of friendly relations with the allies that emerged during the First World War and that developed during the years of struggle against the “Bolshevik-German armies.” Ivanov’s second article, a response to the events in Vladivostok in the Fall 1919 — particularly, to the secret support of the anti-government conspiracy of the Socialist-Revolutionaries and Bolsheviks on behalf of the allied forces — calls for the necessity to concentrate Russia’s forces and to strengthen Russia’s place in the international arena. The present article shows how Ivanov’s position about the allies developed under the 1919 Siberian circumstances, was reflected in his literary work. For example, it analyzes a plot line associated with the treacherous behavior of the Japanese lieutenant Tanako Muzzi that first appeared in the “The Armored Train 14-69” and then got developed in the homonymous play.